Descriptive Epidemiology of Unintentional Burn Injuries Admitted to a Tertiary-Level Government Hospital in Nepal: Gender-Specific Patterns. (July 2015) - Sharma, Narayan Prasad; Duke, Janine M.; Lama, Bir Bahadur; Thapa, Buland; Dahal, Peeyush; Bariya, Nara Devi; Marston, Wendy; Wallace, Hilary J.
This study describes the epidemiology of unintentional adult burn injury admissions in a tertiary hospital in Nepal, from 2002 to 2013, focusing on gender-specific patterns. Chi-square tests and Wilcoxon Rank Sum tests were performed. There were 819 unintentional burn admissions: 52% were male and 58% younger than 35 years. The median percentage total body surface area burned (interquartile range) was greater in females than in males ( P < .001): 28% (17-40) versus 20% (12-35), and female mortality was higher (32% vs 11%). A higher proportion females were illiterate than males (48% vs 17%). Burns occurred at home (67%), work (28%), and public places (5%); gender-specific patterns were observed. Flame burns accounted for 77%, electricity 13%, and scalds 8%. Kerosene (31%) and biomass (27%) were the major fuels. Cooking, heating, and lighting were the main activities associated with burn injury. Results support interventions to reduce the use of open fires and kerosene and to promote electrical safety.